Water absorption and drying shrinkage of recycled foamed aggregate concrete - Chai, Teck Jung; Tang, Hing Kwong; Koh, Heng Boon (Penerbit UTM Press, 2018)
This paper presents some experimental results and discusses the used of recycled foamed aggregates as natural coarse aggregates replacement in producing concrete. The physical properties of recycled foamed aggregates concrete were investigated. The properties studied are water absorption and drying shrinkage from the concrete early ages until the periods of 56 days. The 100 mm x 100 mm cube specimen was used to study the water absorption at the age of 7, 28 and 56 days. Meanwhile, the 100 mm x 100 mm x 300 mm length prism had been casted and used for drying shrinkage test for recycled foamed aggregates concrete. The foamed aggregates was produced from crushing recycled foamed concrete blocks. It were coated with cement paste to reduce its water absorption ability during casting process. Superplasticizer was used to maintain the workability of fresh concrete with a slump vary between 50 mm to 100 mm. The physical tests were conducted on recycled foamed aggregates to determine their initial properties such as loose bulk density, sieve analysis and water absorption rate. Recycled foamed aggregate concretes were produced with varied water cement ratio. The results obtained indicated that the linear elastic relationship between water cement ratio and water absorption rate. The higher the water cement ratio of concrete specimen will obtained higher water absorption rate. Vice versa, the density is low for drying shrinkage. The water absorption decreased while drying shrinkage becomes more stabilized over curing period.